The role of Legal Aid NSW in addressing the civil legal needs of participants in High Intensity Units (HIPUs) in prisons. Issue 4 (2nd October 2021) - Lin, Brenda; Clancey, Garner; Metcalfe, Laura
ABSTRACT: Legal Aid NSW civil lawyers provide community outreach clinics and civil legal assistance to address the civil legal needs of participants in High Intensity Program Units (HIPUs) in prisons in New South Wales (NSW), Australia. Semi-structured interviews were conducted with Legal Aid NSW staff to explore their work in HIPUs. Interviews focused on the types of civil legal issues faced by HIPU participants, the value of providing such services in the HIPUs and the challenges and barriers associated with this work. The findings indicated that HIPU participants have a range of civil legal needs including issues relating to housing and tenancy, outstanding debts, welfare payments, victims' compensation, driver disqualification, tort claims and family law matters. Successful resolution of these matters can be critical for ensuring the best chance of post-release desistance from crime. However, provision of civil legal services in prisons can be adversely impacted by practical and operational issues attributable to the time- and resource-intensive nature of this work. Some of these barriers include considerable travel times to prison, delays upon arrival at the prison and unexpected lockdown procedures.